Evaluasi Tata Kelola Teknologi Informasi Dinas Komunikasi dan Informatika Kabupaten Bogor Menggunakan Kerangka Kerja COBIT 4.1 dengan Domain Plan and Organise (PO) dan Acquire and Implement (AI) - Agung Prasetyo Siregar; Suprapto Suprapto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Diskominfo Kabupaten Bogor is a institution that organizes Government affairs in the field of Communication and Information Technology. The field of E-Government Implementation is one of the divisions in Diskominfo Kabupaten Bogor which has the authority assist the Head of institution in the drafting and implementing policies, so that it need to have good IT governance. From the results of the interviews, there were found problems in IT governance, such as not having SOP (Standard Operating Procedure), lack of HR (Human Resources) with a bachelor's background in IT, HR knowledge is lack, maintenance of IT infrastructure is lack, absence of risk management. This research determine the result maturity IT governance in Diskominfo Kabupaten Bogor using COBIT4.1 framework which focuses on Plan and Organize (PO) and Acquire and Implement (AI). The results of research, found that the maturity level for the PO domain is 1.90 and the AI ​​domain is 1.71. To increase the maturity level value as expected, recommendations were made that could be applied to the Diskominfo Kabupaten Bogor. Some of the recommendations such as making SOP documents, giving sosialisation to human resources to support existing IT processes, making technology standards that are used as guidelines to establish the direction technology and maintenance of IT infrastructure, and documenting risk management that might occur.